Basics of Language for Language Learners : Literature, Language, and Aesthetics - Culicover, Peter W.; Hume, Elizabeth V., 1956- (Book collections on Project MUSE., 2010)
"Learning a language involves so much more than just rote memorization of rules. Basics of Language for Language Learners ... by Peter W. Culicover and Elizabeth V. Hume, systematically explores all the aspects of language central to second language learning: the sounds of language, the different grammatical structures, the social functions of communication, and the psychology of language learning and use. Unlike books specific to one single language, Basics of Language will help students of all languages. Readers will gain insight into the structure and use of their own language and will therefore see more clearly how the language they are learning differs from their first language. Language instructors will find the approach provocative, and the book will stimulate many new and effective ideas for teaching. Both a textbook and a reference work, Basics of Language will enhance the learning experience for anyone taking a foreign language course as well as the do-it-yourself learner"--From publisher's description.